Patient-reported minor adverse events after colonoscopy: a systematic review. (1st April 2019) - Steffenssen, Mia W.; Al-Najami, Issam; Baatrup, Gunnar
Abstract: Objective: The purpose of this systematic review was to investigate the incidence and nature of minor adverse events (MAEs) after colonoscopy, and response rates to questionnaires concerning MAEs in patients undergoing colonoscopy. Materials and methods: A systematic literature search was conducted in the databases PubMed and Embase. Predictor variables were patient-reported MAEs after colonoscopy. The outcome was frequency and types of MAEs and the patients' response rate to questionnaires after colonoscopy. Quality assessment for potential risk of bias and level of evidence was evaluated using the National Health and Medical Research Council guidelines. Results: Seven prospective cohorts were included with a pooled total of 6172 participants. Patients undergoing colonoscopy had a response rate to questionnaires ranging from 64% to 100%, with a mean of 81%. One-third of the patients experienced MAEs, most prominently in the first 1–2 weeks after colonoscopy, and less common at 30 days post colonoscopy. The most frequently reported MAEs were abdominal pain, bloating and abdominal discomfort. Conclusions: In general, patients undergoing colonoscopy have a high response rate to questionnaires about MAEs. MAEs after colonoscopy are commonly seen. High age and score of American Society of Anesthesiologists (ASA) classification, female gender and duration of procedure seem to be associated with a higher risk of MAEs, whereas adequate sedation seems to decreases the risk. MAEs after colonoscopy seems to be underreported in the current literature and the existing evidence is based on inhomogeneous reports. In the current study, it was not possible to conduct a meta-analysis. There is a need for larger scale studies addressing the MAEs patients experience in conjunction with a colonoscopy. Furthermore, the assessment of the MAEs should rely on questionnaires tested for validity, comprehensibility and reliability, to reflect the patient-reported experience of a colonoscopy as precise as possible.